An Investigation of the Differential Effects of Ursane Triterpenoids from Centella asiatica, and Their Semisynthetic Analogues, on GABAA Receptors. (10th May 2016) - Hamid, Kaiser; Ng, Irene; Tallapragada, Vikram J.; Váradi, Linda; Hibbs, David E.; Hanrahan, Jane; Groundwater, Paul W.
Abstract : The ursane triterpenoids, asiatic acid1 and madecassic acid2, are the major pharmacological constituents of Centella asiatica, commonly known as Gotu Kola, which is used traditionally for the treatment of anxiety and for the improvement of cognition and memory. Using the two‐electrode voltage‐clamp technique, these triterpenes, and some semisynthetic derivatives, were found to exhibit selective negative modulation of different subtypes of the GABAA receptor expressed in Xenopus laevis oocytes. Despite differing by only one hydroxyl group, asiatic acid1 was found to be a negative modulator of the GABA‐induced current at α 1 β 2 γ 2L, α 2 β 2 γ 2L and α 5 β 3 γ 2L GABAA receptors, while madecassic acid2 was not. Asiatic acid1 exhibited the greatest effect at α 1 β 2 γ 2L (IC50 37.05 μ m ), followed by α 5 β 3 γ 2L (IC50 64.05 μ m ) then α 2 β 2 γ 2L (IC50 427.2 μ m ) receptors. Conversion of the carboxylic acid group of asiatic acid1 to a carboxamide group (2 α, 3 β, 23‐trihydroxy‐urs‐12‐en‐28‐amide5 ) resulted in enhanced inhibition at both the α 1 β 2 γ 2L (IC50 14.07 μ m ) and α 2 β 2 γ 2L receptor subtypes (IC50 28.41 μ m ). The results of this study, and the involvement of α 5 ‐containing GABAA receptors in cognition and memory, suggest that asiatic acid1 may be a lead compound for the enhancement of cognition and memory. Abstract : The ursane triterpenoids, asiatic acid1 and madecassic acid2, exhibit selective negative modulation of different subtypes of the GABAA receptor expressed in Xenopus laevis oocytes. Despite differing by only one hydroxyl group, asiatic acid1 was shown to be a negative modulator of the GABA‐induced current at α 1 β 2 γ 2L (IC50 37.05 μ m ), followed by α 5 β 3 γ 2L (IC50 64.05 μ m ) then α 2 β 2 γ 2L (IC50 427.2 μ m ) GABAA receptors, while madecassic acid2 is not.